Development of standardization methods of gel with sapropel extract and their validation - Strus, Oksana; Revyatskyy, Ivan; Holota, Serhii; Gushcha, Sergey (Current Issues in Pharmacy and Medical Sciences, 2023)
Humic acids (HA) are important natural compounds that are characterized by a wide range of biological activity and therapeutic impact on different pathological processes. Sapropels are natural healing resources that contain a large amount of HA. The pharma-ceutical market of Ukraine needs domestic drugs with dermatotropic action based on natural compounds that have a combined antibacterial, wound healing and anti-inflammatory activity, as well low toxicity. The aims of the research: standardization of the gel under the conditional name "Saprogel" for use in medicine as a wound-healing and anti-inflammatory agent, development of methods for identification and quantification, as well as their validation. A linear dependence between the concentration of the total mass fraction of HA on the mass of the sample of aqueous sapropel extract (ASE) with a correlation coefficient of 0.9985 (≥0.9981) was observed, while the angular coefficient of linear dependence (b) was found to be 1.02, with the free member of linear dependence (a) being – 1.66≤2.60. The obtained results show that the method is precise because the value of the relative confidence interval is less than the critical value for the convergence of the results: Δ%=1.27≤1.60 and the criterion of the insignificance of systematic error: δ=0.51. As a result of the quantitative analysis, we found that the total mass fraction of HA in the gel samples from the wind farm is 1.302%.